Analisis tentang sengketa merek PRADA dengan merek THE RICH PRADA - Clarence Ritch Sutjipto (Fakultas Hukum Universitas Surabaya, 2020)
Abstract This article riviews Trademark cases about extension of the PRADA brand owned by PRADA S.A. and re-registration of THE RICH PRADA brand based on Trademark Law No. 15 of 2001 which is now changed to Law No. 20 of 2016 of Trademark. Therefore, there is a Directorate General of IPR that carries out its duties and functions in the process of trademark registration and others. The case discussed in this article is regarding PRADA brand owned by PRADA S.A. who registered their brand in class 43 in 2007, but until 2017 PRADA S.A. absolutely not produce in class number 43. And an extension in 2018, and re-registration of THE RICH PRADA mark in indication of bad faith, the research method used in this article is normative juridical research that is research conducted with literature study, which refers to legal materials both primary and secondary legal materials related to this article. The results of the article shows that if there are registered trademarks that register trademarks in the brand class but not used at all, it can still be extended as long as they do not exceed the grace period and in the registration of the mark, it should be in good faith.